Examine the Frequency of Diabetes Mellitus and Glucose Intolerance in Patients with Lichen Planus - Afsheen Bilal, Jahangir Khan, Syeda Ujala Sohail, Yumin Xia, Zille Huma, Khurram Nadeem (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: The purpose of this study was to determine whether or not individuals with LP also had a high incidence of diabetic mellitus (DM) and/or glucose intolerance. Study Design: Cross-sectional study Place and Duration: This study was conducted at Abbottabad Medical Complex Hospital, Abbottabad in the duration from April, 2021 to October, 2021. Methods: Total 67 patients of both gender had lichen planus were presented in this study. After getting informed written consent detailed demographics of enrolled cases included age, sex, body mass index and duration of LP were recorded. Fasting blood sugar levels between 100 and 125 mg/dL (5.6 and 7.0 mmol/L) were considered to be indicative of impaired fasting glucose (IFG). Frequency of DM and glucose intolerance were recorded. SPSS 23.0 was used to analyze all data. Results: In this study, 36 (53.7%) were males and 31 (46.3%) were females. The mean age of the patients was 51.3±17.87 years and had mean BMI 26.08±12.63 kg/m2. Mean duration of LP was 3.9±10.29 years. There were 28 (41.8%) cases had classic lichen planus, followed by ashy dermatosis, hypertrophic, oral lichen planus, nail and actinic. We found that 17 (25.4%) patients had diabetes mellitus type II and 20 (29.9%) cases had glucose intolerance. We found a significant relationship between LP and DM in our cases with p value <0.004. Conclusion: We concluded in this study that the patients of lichen planus had higher frequency of DM type -2 and glucose intolerance. There was a close relationship between lichen planus and DM among all cases. There is need to evaluate patients early for treatment in hospitals. Keywords: Glucose Intolerance, type-2 DM, Lichen planus